2004
DOI: 10.1073/pnas.0307900100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modulation of calcium oxalate crystallization by osteopontin and citrate

Abstract: Calcium oxalate monohydrate (COM), which plays a functional role in plant physiology, is a source of chronic human disease, forming the major inorganic component of kidney stones. Understanding molecular mechanisms of biological control over COM crystallization is central to development of effective stone disease therapies and can help define general strategies for synthesizing biologically inspired materials. To date, research on COM modification by proteins and small molecules has not resolved the molecular-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
391
3
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(428 citation statements)
references
References 22 publications
25
391
3
9
Order By: Relevance
“…AFM imaging has proven to be a powerful tool for real-time visualization of crystal growth on specific faces of organic and inorganic crystals (21)(22)(23)(24), including COM (15,25). AFM imaging also has been used to obtain images of kidney stones (26).…”
Section: Resultsmentioning
confidence: 99%
“…AFM imaging has proven to be a powerful tool for real-time visualization of crystal growth on specific faces of organic and inorganic crystals (21)(22)(23)(24), including COM (15,25). AFM imaging also has been used to obtain images of kidney stones (26).…”
Section: Resultsmentioning
confidence: 99%
“…Four mechanisms have been proposed for crystallization modulation through impurity (including organic and inorganic molecules) interactions: (1) step pinning [45], (2) incorporation [34], (3) kink blocking, and (4) step-edge adsorption. Each of these major mechanisms for growth inhibition exhibits a characteristic dependence of step speed on supersaturation and impurity concentration [35].…”
Section: Crystallization and Dissolution Modulation Of Calcium Orthopmentioning
confidence: 99%
“…[1,2] One prevailing view is that mineral-associated macromolecules are responsible for initiating and stabilizing non-equilibrium crystal polymorphs and morphologies through interactions between anionic moieties and cations in solution or at mineral surfaces. [3][4][5][6] Indeed, numerous studies have demonstrated that bio-organic additives can dramatically alter crystal shapes and growth-rates in vitro. However, previous molecular-scale studies revealing mechanisms of growth modification focused on small molecules such as amnio acids or peptides and always observed growth inhibition.…”
mentioning
confidence: 99%